G+ COMMUNITY: MEASURING TEACHERS’ READINESS AND ACCEPTANCE - Mohd Faisal Farish Ishak; Rashidah Rahamat; Muhammad Hazrul Haris Fadzilah; Abdul Ghani Abu (Universitas Islam Sultan Agung, 2017)
The purpose of this paper is to explore teachers’ acceptance and readiness in using the cloud-based community as a platform for professional collaboration related to their teaching and learning. Familiarity with certain social networking platforms has made the preferable collaboration among teachers only limited to using Facebook, WhatsApp or Telegram. However, with time and space constraints in schools, some of the sharing sessions could not be done effectively most of the time. The study focuses on teachers’ acceptance and readiness of having their community in the cloud when they were introduced to the platform during a Continuous Professional Development (CPD) course. A total number of 61 teachers used Google Community named as ‘Contemporary Children’s Literature (CCL) 2016’ as a platform for their Professional Learning Community (PLC) during the course. Descriptive analysis was done using Google Sheets and the findings show that these teachers are receptive towards Google Community in terms of its engagement level, usefulness as well as ease of use. The introduction to Google Community has created a new pathway for their collaboration especially for teaching and learning purposes. In a nutshell, their acceptance towards the cloud-based community indicates that, given the right training channel, teachers are positive and opened to utilising and integrating the cloud-based technology in their current teaching practice.